2017
DOI: 10.21101/cejph.a4305
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence vs. Mental Load in Nurses Working at a Chemotherapy Ward

Abstract: Longer work experience and lower levels of Coherence are associated with higher risk for mental overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 2 publications
3
16
1
2
Order By: Relevance
“…An interesting point was explored by Kretowicz et al, who correlated positively SOC and educational background: as SOC is considered to have an educational value and the progress in the academic education could elevate it, it is reasonable to think that this relationship could influence task completion in managerial positions [7]. Furthermore, Antonovsky did not exclude a possible influence of negative life events on SOC, especially for those with low or moderate SOC [42].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An interesting point was explored by Kretowicz et al, who correlated positively SOC and educational background: as SOC is considered to have an educational value and the progress in the academic education could elevate it, it is reasonable to think that this relationship could influence task completion in managerial positions [7]. Furthermore, Antonovsky did not exclude a possible influence of negative life events on SOC, especially for those with low or moderate SOC [42].…”
Section: Discussionmentioning
confidence: 99%
“…Educational background, considered by Kretowicz et al was found to be positively associated to overall SOC and Meaningfulness [7]. Two studies by Debska et al and Lewis et al have not proven the same correlation [6,8].…”
Section: Individual Characteristicsmentioning
confidence: 91%
See 3 more Smart Citations